Formal analysis of a space-craft controller using SPIN. - Havelund, K. (IEEE Transactions on software engineering)
The paper documents an application of the finite state model checker SPIN to formally analyze a multithreaded plan execution module. The plan execution module is one component of NASA's New Millennium Remote Agent, an artificial intelligence-based spacecraft control system architecture which launched in October of 1998 as part of the DEEP SPACE 1 mission. The bottom layer of the plan execution module architecture is a domain specific language, named ESL (Executive Support Language), implemented as an extension to multithreaded COMMON LISP. ESL supports the construction of reactive control mechanisms for autonomous robots and spacecraft. For the case study, we translated the ESL services for managing interacting parallel goal-and-event driven processes into the PROMELA input language of SPIN. A total of five previously undiscovered concurrency errors were identified within the implementation of ESL. According to the Remote Agent programming team, the effort has had a major impact, locating errors that would not have been located otherwise and, in one case, identifying a major design flaw. In fact, in a different part of the system, a concurrency bug identical to one discovered by this study escaped testing and caused a deadlock during an in-flight experiment, 96 million kilometers from Earth. The work additionally motivated the introduction of procedural abstraction in terms of inline procedures into SPIN